Concepts related to the economic security of service enterprises - Aminov Zarif Yusupovich (Genius Journals, 2022)
The issue of economic security of enterprises, including service enterprises, has a special place in the security system. Because this is not only an economic issue, but also an important social one. This cannot be achieved by performing one or more activities at a given time. This goal can be achieved by applying a set of measures that are usually thought out, routinely and consistently implemented.This article discusses security and related terms.
Keywords: Security; Economic Security; Loss; Profit